Lord of shadows - Clare, Cassandra (Clare, Cassandra. Dark artifices, 2017)
Emma is torn between her passion for Julian and her need to protect him from the consequences of a forbidden romantic partnership, a situation challenged by her relationship with Mark and his efforts to regain his Shadowhunter capabilities.